TRANSLATION PROBLEMS OF ECONOMIC TERMS FROM ENGLISH INTO UZBEK - Djumambetova Gulziba, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article is devoted to the study of the translation peculiarities of economic terms from English into the Uzbek language. This study has particular significance as it has been investigated metaphorical terms in the sphere of economics, in the context of translation difficulties lying in the base of their different perception from English into Uzbek. In order to make an accurate translation it is very important to pay attention to metaphorical terms in both languages.